Morphometric and hydrographie characteristics of torrents of NW Péloponnèse, Greece - Pagonas, M.; Kontopoulos, N. (Bulletin of the Geological Society of Greece, 2007)
The study area includes the catchments of Selemnos, Xylokeras and Volinaios torrents, with 456 streams of 277.848 km total length. The pattern is generally dendritic. A quantitative analysis of the drainage systems of the study area was interpreted and then correlated to the fault systems that appear in the area. The main direction of the streams and the tectonic features is WSW-ENE. The drainage density and stream frequency is highly variable as a result of many factors, most important of which is lithology with high infiltration capacity. The number and the length of most streams show divergence of the 1st and 2nd law of Horton since they have dissimilar values from those theoretically expected.